Pengaruh Capital Adequacy Ratio Dan Non Performing Loan Terhadap Nilai Perusahaan Pada PT. Bank Jago, Tbk. - mutmainna, nuramalia; Afriyani; Andriani Yasin, Nurfatwa (LPPM STIE Tri Dharma Nusantara - Makassar, 2025)
The purpose of this study is to determine the Effect of Capital Adequacy Ratio and Non-Performing Loan on the value of the company in PT. Bank Jago, Tbk. The types of data used in this study are qualitative and quantitative. The data source used in this study is secondary data. The analysis methods used are descriptive analysis and multiple linear regression, determination coefficient (R2), correlation coefficient (r), t test, and F test. The results of this study show the regression equation Y = 10,280 + 0,064X1 – 2,589X2, determination coefficient, (R2) = 37,3% and correlation coefficient (R) = 0,611. Capital Adequacy Ratio and Non Performing Loan simultaneously it does not have a significant influence on the company's value. Partially, the Capital Adequacy Ratio has a positive and significant effect on the company's value in PT. Bank Jago, Tbk. Non-Performing Loanshave a significant effect on the company's value at PT. Bank Jago, Tbk. hypothesis 1 and hypothesis 2 are not accepted, Hypothesis 3 is accepted.